World Population Situation with Special Reference to SAARC Countries - Acharya, Pitambar (Journal of Development and Administrative Studies, 2018)
The main objective of this article is to analyze the demographic situation of SAARC countries. This article is based on descriptive analyses of the data derived from the World Population Data Sheet (Population Reference Bureau) 2006 and 2016. The world population reached 7.4 billion in 2016. It is unevenly distributed because less developed countries occupied 83 percent and more developed countries had 17 percent. Asia only occupied three-fifth (60.53%). In the SAARC region, India and Maldives are the countries with the highest and lowest population. Afghanistan had the highest fertility and mortality whereas Sri Lanka and Maldives had the lowest fertility and mortality. Sri Lanka, Maldives, and Bangladesh had life expectancy over 70 years. Afghanistan and Sri Lanka had the highest (44%) and lowest (25%) shares of the young population. However, the share of the old dependent population (65+ years) in the SAARC region was very low. Similarly, the highest and lowest urban percentages were found in Maldives (46%) and Sri Lanka (18%).